1999
DOI: 10.2307/3434469
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling and Cytotoxicity

Abstract: The divalent calcium cation Ca2+ is used as a major signaling molecule during cell signal transduction to regulate energy output, cellular metabolism, and phenotype. The basis to the signaling role of Ca2+ is an intricate network of cellular channels and transporters that allow a low resting concentration of Ca2+ in the cytosol of the cell (lCa2+1) but that are also coupled to major dynamic and rapidly exchanging stores. This enables extracellular signals from hormones and growth factors to be transduced as IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 87 publications
(71 reference statements)
3
52
0
Order By: Relevance
“…It will be interesting to investigate the route of Ca 2ϩ entry for these phenomena. We previously demonstrated that in U937 cells MFs increase cell survival from damaging agents via increased Ca 2ϩ influx because MFs failed to exert their anti-apop- (24). This apparent paradox might be explained by considering the role played in apoptosis by the endoplasmic reticulum, the main intracellular Ca 2ϩ store whose integrity is maintained by a proper intralumenal Ca 2ϩ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to investigate the route of Ca 2ϩ entry for these phenomena. We previously demonstrated that in U937 cells MFs increase cell survival from damaging agents via increased Ca 2ϩ influx because MFs failed to exert their anti-apop- (24). This apparent paradox might be explained by considering the role played in apoptosis by the endoplasmic reticulum, the main intracellular Ca 2ϩ store whose integrity is maintained by a proper intralumenal Ca 2ϩ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…These include oxidative metabolism of AA to biologically active eicosanoids and/or reactive oxygen species [8,9,14], induction of the mitochondrial permeability transition [13,17], accumulation of cellular ceramides [10,11] and intracellular calcium regulation [12]. An increase of intracellular calcium may aggravate the mechanism of cell injury and accelerate the time of onset of the mitochondrial permeability transition [18,19], and activate Ca 2+ -dependent hydrolases such as calpain and phospholipase A2 [20]. The role of calcium in AA-induced cytotoxicity seems to depend on the experimental model under study, as increased release of calcium from intracellular stores was related to AA-dependent cell death in a neuronal cell line [12], but Ca 2+ influx was not involved in AA toxicity in PC12 cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although intracellular calcium has been suggested to play a role in the oxidative damage of hepatocytes, the effects and source of the oxidative stress-induced intracellular Ca 2ϩ increase are currently debatable (6). Treatment of liver cells with several oxidative stress inducer drugs increases [Ca 2ϩ ] i and produces cell toxicity through necrosis and/or apoptosis, depending on the degree of exposure (dose and duration) (2). The initial source of Ca 2ϩ depends on the specific oxidant and cell type employed, since certain toxins cause calcium release from intracellular stores (5, 7), whereas others cause Ca 2ϩ influx from the extracellular space (6,8).…”
mentioning
confidence: 99%
“…According to the calcium hypothesis of cell injury, a perturbation of intracellular Ca 2ϩ homeostasis leading to a sustained increase in cytosolic Ca 2ϩ is an early and critical event in the development of toxicity in hepatocytes exposed to oxidative stress, causing the ultimate loss of cell viability through activation of various Ca 2ϩ -dependent processes (1,2). Increases of [Ca 2ϩ ] i can result from an influx of Ca 2ϩ from the extracellular medium, redistribution of Ca 2ϩ from intracellular stores, or both influx and redistribution.…”
mentioning
confidence: 99%